Verification of Phase Space Inversions Based on The Initial Conditions of the Chaotic Chen System - Ali, Nabaa Mohammed; Jamal, Raied K. (Iraqi Journal of Science, 2023)
Theoretically, an eight-term chaos system is presented. The effect of changing the initial conditions values on behavior Chen system was studied. The basic dynamical properties of system are analyzed like time series, attractor, FFT spectrum, and bifurcation. Where the system appears steady state behavior at initial condition xi , yi , zi equal (0, 0, 0) respectively and it convert to quasi-chaotic at xi ,yi ,zi equal (-0.1, 0.5,-0.6). Finally, the system become hyper chaotic at xi ,yi ,zi equal(-0.5, 0.5,-0.6 ) that can used it in many applications like secure communication.